Living, Caring, Learning – Setting boundaries for the wellbeing of everyone in bleeding disorders care - Harrison Cathy (The Journal of Haemophilia Practice)
Cathy, a haemophilia nurse specialist in the UK, reflects on a challenging patient with a rare inherited platelet disorder. The patient did not attend regular clinic appointments, and when presenting at clinic due to severe bleeding or feeling unwell was often aggressive and abusive towards staff. The care team were concerned that he was putting his health at risk and followed protocols for vulnerable adults to try and ensure he was accessing the care he needed. This involved bringing in expertise outside of the multidisciplinary team (MDT), including non-medical services. Steps were also taken to ensure staff safety and wellbeing through in-house psychological support and the agreement of strategies for dealing with difficult behaviour. Ultimately, it was necessary to find an alternative care pathway for the patient. While acknowledging her disappointment in this outcome, Cathy reflects on how the processes followed have reinforced the development of individualised care plans for all patients with complex needs, and the importance of access to specialist services beyond the MDT. She also highlights considerations around the safety and wellbeing of the care team, the role of discussion and ‘debriefing’, and the value of staff access to psychological support.